Deployment strategies for FTTH networks and their impact on the business case: A comparison of case studies - Albert Domingo; Marlies Van der Wee; Sofie Verbrugge; Miquel Oliver (International Telecommunications Society (ITS), 2014)
Although it is clear that the evolution of fixed access networks requires the installation of Fiber-to-the-Home (FTTH) to all households, the business case for deploying such networks is very uncertain. It requires significant upfront investment, while not being assured of sufficient timely revenues to cover for it. Although many studies focus on modeling the costs and forecasting the revenues, limited research deals with how both sides can impact the overall business case. This paper compares different deployment strategies used in current FTTH network rollouts, and examines their impact on the overall business case. Deployment strategies are defined as ways to plan the installation of the network and uptake over time, influenced by a variety of situation-dependent characteristics. By studying the different parameters that allow characterizing and grouping ongoing FTTH projects worldwide, we can analyze what drove the choice for the deployment strategy, and how the latter impacts both cost and revenue side of the business case. The paper concludes that deployments driven by demand are less risky and therefore more sustainable. On the other hand, publicly funded or initiated projects obey to different goals than demand and can be unsustainable if they are not able to engage the planned penetration rates.
Keywords: 330; Fiber-to-the-Home; techno-economics; business case; deployment strategy